2006
DOI: 10.1002/path.2026
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of the expression of the novel stem cell marker CDCP1 in cancer cells

Abstract: CDCP1 is a novel stem cell marker that is expressed in several types of cancer. The mechanisms by which CDCP1 expression is regulated, and the clinical implications of this marker, have not been clarified. In this report, we examine the epigenetic regulation of CDCP1 expression in cell lines and clinical samples from patients with breast cancer. Many CpG sequences were localized around the transcription initiation site of CDCP1. These CpG motifs were found to be poorly methylated in cell lines with high levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 17 publications
5
44
1
Order By: Relevance
“…It was also identified as CDCP1, an mRNA transcript that is up-regulated in colon and lung cancer [38], as well as skeletal muscle, colon, and various human tumor lines [39,40]. Current observations suggest that CDCP1 expression negatively correlates with the amount of methylation found at the promoter region [41], but only weakly correlates with the metatstatic potential of cell lines [39]. Further, Gp140 is regulated at the protein level through SFK-dependent phosphorylation (Zaitsevakaia et al, manuscript in preparation).…”
Section: Signaling Through Gp140/cdcp1 Requires Components Of Drms Anmentioning
confidence: 85%
“…It was also identified as CDCP1, an mRNA transcript that is up-regulated in colon and lung cancer [38], as well as skeletal muscle, colon, and various human tumor lines [39,40]. Current observations suggest that CDCP1 expression negatively correlates with the amount of methylation found at the promoter region [41], but only weakly correlates with the metatstatic potential of cell lines [39]. Further, Gp140 is regulated at the protein level through SFK-dependent phosphorylation (Zaitsevakaia et al, manuscript in preparation).…”
Section: Signaling Through Gp140/cdcp1 Requires Components Of Drms Anmentioning
confidence: 85%
“…For example, as part of the initial report on the CDCP1 gene and coding sequence, elevated CDCP1 mRNA levels were detected in several solid tumors including colon, lung, and breast cancers relative to unmatched normal tissues (1). Further support for increased CDCP1 expression in breast cancer came from a study which, although providing no comparison with normal breast tissue, showed that CDCP1 mRNA levels inversely correlated with methylation of the CDCP1 transcription initiation site in all 25 breast cancer patient samples examined (12). Consistently, immunohistochemical analysis of two breast cancer samples demonstrated that a patient with high CDCP1 mRNA levels had correspondingly high CDCP1 protein levels that correlated with high expression of the proliferation marker Ki67, while a patient with low CDCP1 mRNA levels had correspondingly low CDCP1 and Ki67 protein levels (12).…”
Section: Dysregulated Expression Of Cdcp1 In Solid Tumorsmentioning
confidence: 94%
“…Further support for increased CDCP1 expression in breast cancer came from a study which, although providing no comparison with normal breast tissue, showed that CDCP1 mRNA levels inversely correlated with methylation of the CDCP1 transcription initiation site in all 25 breast cancer patient samples examined (12). Consistently, immunohistochemical analysis of two breast cancer samples demonstrated that a patient with high CDCP1 mRNA levels had correspondingly high CDCP1 protein levels that correlated with high expression of the proliferation marker Ki67, while a patient with low CDCP1 mRNA levels had correspondingly low CDCP1 and Ki67 protein levels (12). In another small study, analysis of colon adenocarcinoma and adjacent nondiseased tissue from three patient samples indicated a potential link between more malignant colon cancer cells and CDCP1 staining intensity, although a conclusive association could not be demonstrated from such a small cohort (2).…”
Section: Dysregulated Expression Of Cdcp1 In Solid Tumorsmentioning
confidence: 99%
See 2 more Smart Citations